Dietary Change and Global Sustainable Development Goals - Chen, Canxi; Chaudhary, Abhishek; Mathys, Alexander (Frontiers in Sustainable Food Systems, 2022)
Food production for human consumption is a leading cause of environmental damage in the world and yet over two billion people suffer from malnutrition. Several studies have presented evidence that changes in dietary patterns across the world can lead to win-win outcomes for environmental and social sustainability and can complement ongoing technological and policy efforts to improve the efficiency of agricultural production. However, the existing evidence have been compiled in ‘silos’ by a large range of researchers across several disciplines using different indicators. The aim of this quantitative review is to bring together the existing knowledge on heterogeneity of current dietary patterns across the world and how a transition towards healthy diets in different countries can aid in progress towards multiple global Sustainable Development Goals (SDGs). We first summarize the nutritional quality, economic cost, and environmental footprint of current diets of over 150 countries using multiple indicators. Next, we review which shifts in dietary patterns across different world regions can help towards achievement of SDG2 (Zero hunger), SDG3 (Good health and well-being), SDG 6 (Clean water and sanitation), SDG13 (Climate action), SDG14 (Life below water), and SDG15 (Life on land). Finally, we briefly discuss how to enable the shift towards sustainable dietary patterns and identify the research and data gaps that need to be filled through future efforts. Our analysis reveals that dietary change is necessary in all countries as each one has unique priorities and action items. For regions such as Sub-Saharan Africa and South Asia, increased intake of nutrient dense foods is needed to address deficiency of essential nutrients like folate, potassium, and vitamin A. For North America and Europe, shifting towards more plant-based diets would be healthier and simultaneously reduce the per capita environmental footprints. The results can be useful for policymakers in designing country-specific strategies for adoption of sustainable dietary behaviours and for food industry to ensure the supply of sustainable food items customized with regions’ need.